Impact of Training on Knowledge of Improved Agricultural Practices of Arid Zone - K N. K Chauhan, R. N. Singh and M. P. Singh (Indian Journal of Extension Education, 1990)
Central Arid Zone research Institute is devoted towards creating awareness and utilization of improved arid zone technologiesrecommended by its scientists in dry land agriculture, forestry, grass land development and horticulture. Regular training courses are organised on specific technologies for extension personnel of state department. The study was designed to measure the impact of training courses organised during 1987 on the gain in knowledge of trainees.